'My language, my identity': negotiating language use and attitudes in the New Zealand Fiji Indian diaspora. Issue 1 (2nd January 2019) - Hundt, Marianne
Abstract: One result of colonial and post-colonial migration is the development of large diaspora communities. The Indian diaspora is currently one of the largest world-wide. Over 20 million people of Indian descent live outside of India, many of them in an English-speaking country. Maintenance of the heritage language and use of the majority language are important aspects of identity construction among members of such diaspora communities. Matters become more complex for twice-migrants, i.e. in situations where movement to a secondary diaspora has become necessary. This paper takes up these issues in a case study on the Fiji Indian diaspora in Wellington, New Zealand. Based on data from sociolinguistic interviews, it looks at discursive identity construction around the notion of language use and attitudes towards different languages and their varieties. An important aspect turns out to be the positioning of Fiji Indians not only vis-à-vis speakers of the host community but also relative to Indian migrants who have come to New Zealand directly from the Indian subcontinent.